"To Me, Everybody Is infected": Understanding Narratives about HIV Risk among HIV-negative Black Men Who Have Sex with Men in the Deep South. Issue 6 (12th May 2021) - Denson, Damian J.; Gelaude, Deborah; Saul, Heather; Schoua-Glusberg, Alisú; Randall, Laura A.; Kenward, Katherine; Gall, Elizabeth; Hickson, DeMarc; Schamel, Jay; Frew, Paula M.
ABSTRACT: For black MSM living in the Deep South, the intersection of sexuality, race, and geography impacts HIV risk substantially. Between July and September 2016, we conducted a qualitative study among HIV-negative black MSM in five southern cities in the US with elevated HIV prevalence. Analysis included assessment of interrater reliability, cluster analysis, and descriptive statistics. We enrolled 99 black MSM (mean age: 33.6; SD = 12.8; range: 17–68 years). Four overarching themes emerged: harboring fear of HIV and the internalization of HIV stigma; scrutinizing potential partners to assess riskiness and HIV status; embracing distance and isolation from those perceived as a threat to HIV status; and exhibiting self-efficacy toward HIV prevention and utilizing risk reduction strategies. Future HIV prevention efforts may benefit by balancing risk and deficit based strategies with those that emphasize resilience, address disenfranchisement via structural interventions, and assess and treat inherent trauma(s).